2009
DOI: 10.1188/09.onf.563-570
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Patterns of Fatigue and Quality of Life Over Time Based on Different Breast Cancer Adjuvant Chemotherapy Regimens

Abstract: Clinicians should screen patients for fatigue and assess for contributing factors at clinic visits. Methods to integrate evidence-based fatigue interventions into practice should be tested and outcomes evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 15 publications
6
31
0
5
Order By: Relevance
“…28 When morning and evening fatigue scores were predicted for patients who were one SD above the mean GSDS score (71.6) predicted scores for morning (3.8) and evening (5.8) fatigue were above the clinically meaningful cut-off scores for both symptoms. Taken together, the consistent findings across our studies 5,16,20,23,28,45 and other cross-sectional studies 8,46-49 provide strong evidence of the positive association between sleep disturbance and fatigue severity. Additional research is warranted to determine which symptom is the driver.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…28 When morning and evening fatigue scores were predicted for patients who were one SD above the mean GSDS score (71.6) predicted scores for morning (3.8) and evening (5.8) fatigue were above the clinically meaningful cut-off scores for both symptoms. Taken together, the consistent findings across our studies 5,16,20,23,28,45 and other cross-sectional studies 8,46-49 provide strong evidence of the positive association between sleep disturbance and fatigue severity. Additional research is warranted to determine which symptom is the driver.…”
Section: Discussionsupporting
confidence: 88%
“…In prior studies of patients receiving CTX, there are inconsistent associations between ethnicity and mean daily fatigue scores. 7,8,15,36-38 In addition, definitive conclusions about the asssociation of ethnicity and morning and evening fatigue cannot be drawn given the paucity of studies that evaluated diurnal variations in fatigue severity.…”
Section: Discussionmentioning
confidence: 99%
“…Conclusions about ethnic differences in fatigue severity cannot be drawn because prior studies reported either no differences, 9,10,3941 or higher levels of fatigue in Black patients. 42 Of note in previous studies of patients receiving CTX where no differences in fatigue severity were found, 9,10,3941 90% of the patients were White. The underrepresentation of ethnic minorities in these studies may have limited the power to detect differences in fatigue severity in these patient populations.…”
Section: Discussionmentioning
confidence: 88%
“…Most of the longitudinal studies on fatigue in patients undergoing cancer treatment have evaluated for changes in fatigue severity over the past day, 8 weeks, 9,10 or before and after treatment. 1113 A new and emerging area of research is an evaluation of diurnal variations in fatigue severity.…”
Section: Introductionmentioning
confidence: 99%
“…Existen otros factores que intervienen en la manera de afrontar dicho evento, entre los que se tiene, a la patología y el tipo de tratamiento otorgado (8,14,15) , a las características propias del paciente (edad, estado civil, escolaridad, ocupación, nivel socioeconómico) (16) , los relacionados con el ambiente del paciente (tipo de familia, apoyo social, relación satisfactoria con su cónyuge, funcionamiento familiar, satisfacción marital) (16-,23) . A pesar de esto, la medicina en la actualidad al fraccionarse en diferentes especialidades va perdiendo su visión integradora, y en muchas de las ocasiones la paciente con cáncer de mama es manejada solamente desde el ámbito biológico, por lo que vive de manera personal su duelo, y utiliza sus propios recursos para llevar a cabo el afrontamiento (24,25) . Pocos son los países que tienen dentro de sus sistemas de salud un programa psicooncológico bien estructurado que le permita a estas pacientes tener una visión más adaptativa de su enfermedad (26,27) .…”
Section: Introductionunclassified